2016
DOI: 10.5755/j01.ms.22.2.7330
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Recycled Rubber Particles and Silica on Tensile and Tear Properties of Natural Rubber Composites

Abstract: Application of scrap rubber and worn out tires in natural rubber compounds has been studied. The scrap rubber can, however, be recycled and compounded with natural rubber and thus can be generated as a rubber composite. In this work, recycled rubber particles (RRP) were prepared using pulverization process. Then, RRP was blended with natural rubber and silica compounds, and it was synthesized by two-roll mill and hydraulic press at specified operating conditions. The samples ranging from 0 to 40 phr of RRP loa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
3
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 10 publications
1
3
0
Order By: Relevance
“…In comparison, it can be observed that pure silicone rubber specimens possessed the highest tensile strength compared to 12 wt.% Arenga pinnata-silicone biocomposite specimens. A similar behaviour has been reported by Chandran et al, where the increment of fibre content has resulted in lower tensile strength compared to 0 % fibre loading [23]. Fig.…”
Section: Tensile Testsupporting
confidence: 87%
“…In comparison, it can be observed that pure silicone rubber specimens possessed the highest tensile strength compared to 12 wt.% Arenga pinnata-silicone biocomposite specimens. A similar behaviour has been reported by Chandran et al, where the increment of fibre content has resulted in lower tensile strength compared to 0 % fibre loading [23]. Fig.…”
Section: Tensile Testsupporting
confidence: 87%
“…Under vibration, these bonds act as energy dissipation points and increase the damping ratio of the composite by dissipating energy in the form of heat. 39 Moreover, the high damping and energy dissipation features of the tire powder led to the loss of energy in the form of heat under vibration. 18,22,41
Figure 9.The damping ratio of the first three modes for PP/WGRT/CaCO 3 plates with one edge clamped support condition containing different weight percentages of CaCO 3 and WGRT.
…”
Section: Resultsmentioning
confidence: 99%
“…Moreover, nanoparticles tend to be placed at the interface of the tire powder and the polymer matrix, thus enhancing the cross-links density and increasing Young's modulus of ternary nanocomposites. 39 The reduction of Young's modulus of the nanocomposite with 30 wt.% WGRT and 15 wt.% nanoparticles can be assigned to the agglomeration of nanoparticles.…”
Section: Experimental Analysis Of Vibrational Propertiesmentioning
confidence: 99%
“…[28][29][30][31][32][33][34][35][36][37][38][39][40][41][42] Specifically, the laminated composites are gaining importance in mechanical and aerospace applications such as fuel tanks, rocket motor cases, pipes, pressure vessels, and so on, due to their high-specific stiffness and strength. [13,14,[43][44][45][46] These laminated composites show significant properties in comparison with randomly oriented composites. [47] Further, few studies show the effect of water absorption of FML laminates.…”
Section: Introductionmentioning
confidence: 99%